A Decade of the Total Sanitation Campaign : Rapid Assessment of Processes and Outcomes, Volume 2. Annexes - World Bank (Washington, DC, 2014)
The Total Sanitation Campaign (TSC) of the Government of India has been in operation for over a decade (1999 to date). This report analyses primary and secondary data on the TSC to arrive at an understanding of the processes, outputs and outcomes at a national level and across the states; this is compared with the inputs which have gone into the program. These indicators are then compared individually and in combination to benchmark the states, to understand the relative performance of the states. This benchmarking, based on a combination of eight indicators, is undertaken for both states and districts across the country. The purpose of this report is to synthesis the wealth of information available through secondary sources such as the TSC and Nirmal Gram Puraskar (NGP) online monitoring systems and primary surveys of select districts at different points on the performance curve, to understand the processes by which the national TSC guidelines are implemented at state and district levels and how these contribute to the outcomes achieved. The analysis will focus on the successes and challenges faced in implementing the TSC and NGP, identify gaps and lessons learnt, and recommend programmatic approaches through which these can be addressed. The audience for this report includes policy-makers and implementers at national, state and district levels, and the broader sanitation and hygiene community.